Rheumatology Training for Undergraduate Medical Students in Uganda: A Need Assessment Survey - Winnie Kibone; Angel Lisa Nansubuga; Jerom Okot; Richard Buule; Felix Bongomin; Mark Kaddumukasa (Journal of Medical Education and Curricular Development, 2024)
Objectives Despite the rise in the common rheumatological and musculoskeletal disorders (RMDs) in Africa, rheumatology remains an under recognized field with limited training and exposure of medical students. We assessed the knowledge of undergraduate medical students in Uganda on RMDs occurring in our settings. Methods A descriptive cross-sectional study was conducted among clinical year medical students at 9 universities in Uganda offering undergraduate medical degrees in March and April 2022. A self-administered, semistructured questionnaire was used to collect data on sociodemographic characteristics and basic knowledge on RMDs online using KoboToolbox. Sufficient knowledge was defined as a score of ≥50% (pass mark for undergraduate students in Uganda). Multivariable logistic regression was performed using STATA 16 to determine factors associated with knowledge acquisition on RMDs. Results We enrolled 359 medical students from 9 medical training institutes across Uganda. Overall, 126 (35.1%) participants had sufficient knowledge and the overall mean score for all participants was 41.2%. Factors independently associated with sufficient knowledge were: being in fourth (adjusted odds ratio [aOR]: 2.6, 95% confidence interval [CI]: 1.49-4.64, P  < .001) and fifth year (aOR: 2.2, 95% CI: 1.18-4.18, P  = .013) compared to third year of study, awareness of the speciality of rheumatology (aOR: 4.0, 95% CI: 1.96-8.06, P  < .001), formal classes on rheumatology (aOR: 2.0, 95% CI: 1.15-3.35, P  = .012), prior bedside teaching on RMDs (aOR: 2.3, 95% CI: 1.49-3.69, P  < .001), awareness of common RMDs (aOR: 3.2, 95% CI: 1.67-6.04, P  < .001), and having seen a patient with an RMD (aOR: 1.8, 95% CI: 1.14-2.77, P  < .01). Conclusion There was a significant knowledge gap among undergraduate medical students nationwide on rheumatology. There is an urgent need to increase exposure to RMDs for undergraduate medical students to address the rising burden of RMDs in Uganda.